Utilization of Sambau Coastal Area Space as Recreation in Preserving Local Culture - Rangkuty, Gladies Imanda Utami; Brema, Ahmad Riansyah; Suhardi, Rafi Arbarendy; Lee, Vineeta; Teo, Susanto Jefferson (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2025)
Coastal areas have great potential to be developed as recreational spaces that not only attract tourists but also preserve local culture. Sambau Beach in Nongsa, Batam, faces challenges from rapid development that threatens the identity of Kampung Tua, environmental sustainability, and socio-cultural continuity. This study aims to explore how the Sambau coastal area can be utilized as a recreational space that integrates cultural values and sustainable principles. A qualitative descriptive method with a Research-Based Design (RBD) approach was used, combining literature studies, field observations, and contextual analysis. Findings show that local cultural activities, such as the Tepuk Tepung Tawar ceremony, traditional music performances, and exhibitions of local crafts, play a significant role in attracting tourists while maintaining local identity. Based on these findings, design strategies were developed by incorporating culture into spatial planning, including spaces for cultural performances and communal activities. These spaces are designed to resemble traditional balai adat, functioning as cultural landmarks and community hubs. The resulting design concept emphasizes sustainable development based on local wisdom and aims to enhance tourism potential, support environmental conservation, and reinforce cultural identity. These strategies are visualized through conceptual sketches, spatial diagrams, and 3D models.